Lamourouxia (Orobanchaceae) of Mexico - Francisco-Gutiérrez, Antonio; Ruiz-Sanchez, Eduardo; González, Dolores; Lira-Noriega, Andrés (Phytotaxa, 2023)
Lamourouxia is a Neotropical genus currently classified within the tribe Pedicularideae (Orobanchaceae), a clade of root hemiparasitic plants. It comprises 30 species endemic to the Americas. The genus was last studied as a whole in 1972. Some species have not been collected since that date. Half a century later, based on the revision of 1,284 herbarium specimens of Lamourouxia, 119 digitized specimens, and 43 observations of citizen science, here we present an update of the taxonomic classification, nomenclature, diversity, distribution, uses, and ecology of the Lamourouxia species in Mexico, the country with the highest species richness and highest number of endemic species of the genus (26 and 20 species, respectively). Typifications of valid names and synonyms are given. Also, it is presented the change of the name Lamourouxia barbata instead of L. lanceolata. New diagnostic characters, keys for the species, ecological data, and photographs of the species in the field are provided to facilitate the identification and study of the species of this fascinating genus of hemiparasitic plants.